(untitled) (Hekima Review, 2007)
What does the belief by some economists and civil society organizations in the possibility of a world without poverty mean for our Christian faith? How does it challenge Christian theological imagination, Christian practice and the Church today? After an overview of the situation of poverty in the world, this paper attempts to answer this question by proposing a third way of theologizing on poverty, building, among others, on the strengths of liberation theology.